The Effectiveness of Instructional Design by Blended learning of Technological Enlightenment in Educational Technology Subject - األستاذ الدكتور أفراح ياسين محمد الدباغ; المدرس المساعد سامرند حمدامين حسين (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The Effectiveness of Instructional Design by Blended learning of Technological Enlightenment in Educational Technology Subject. This research aims to Investigate the Effectiveness of Instructional Design by Blended learning of Technological Enlightenment for third grade students in Educational colleges in Salahaddin University. To achieve the goals, the researcher followed (Experimental curriculum). The sample consist of (40) students distributed to two groups randomly the first of Experimental groups (20) students and the second is the control group (20) students. To achieve the goals, the researcher designed a Technological Enlightenment test which consist of (55 paragraph), which its type is (multiplechoice and Editorial questions) after suring veracity and constancy. The researcher used (T-test) to measure the differences between the Experimental groups& control groups &have the following results: There are statistically significant difference between the Experimental groups& control groups in the test Technological Enlightenment. The results show the Effectiveness of Instructional Design of Technological Enlightenment. According to this results the researcher concluded some recommendation and suggestions.